Human Resources Development Era Digital Business - Afiah Mukhtar; Masradin, Masradin; Asmawiyah, Asmawiyah; Rahmat, Rahmat; Nurjaya, Nurjaya (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2022)
The purpose of this study is to describe the implementation of human resource management development in the digital era. This type of research is a descriptive qualitative literature study. There are several Human Resource Development Strategies in the Digital Business Age including: 1) The need for talented HR with hard skills and soft skills, 2) Providing Opportunities to Channel Ideas, 3) Appreciation and Awards. 4) Mastery of Digital Technology. 5) Excellent Service. The novelty of the strategy described in human resource development because of the results of the analysis, field conditions, problems and literature searches needed in the digital era